Implementasi Kebijakan Pembatasan Bangunan Akomodasi Wisata dalam Menopang Pariwisata Berkelanjutan - Sujana, Anak Agung Putu Oka (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
This article aims to discuss the urgency and implementation of restrictions on tourist accommodation buildings in the Badung Regency. The research data were obtained through observation, literature study, and in-depth interviews with informants, namely officials, actors, and observers of Bali tourism. Data analysis was carried out descriptively-interpretatively from the perspective of tourism studies. The results of the study show that it is very urgent to restrict tourist accommodation buildings in Badung Regency to anticipate the oversupply of the number of available tourist accommodation rooms, as well as to create a healthy tourist accommodation business situation. Implementation of three policies, namely Regional Regulation No. 2 of 2012; Regional Regulation No. 26 of 2013; and Perbud Badung No. 36 of 2014 has been able to hinder the development of new tourist accommodation buildings, and support sustainable tourism development, namely tourism development that supports environmental conservation efforts (Palemahan), increasing the socio-economic welfare of local communities (pawongan), as well as tourism development that is sustainable. support the preservation and development of Balinese traditions and culture.